Japanese stone monuments and disaster memory – perspectives for DRR. Issue 6 (17th January 2022) - Garnier, Emmanuel; Lahournat, Florence
Abstract : Purpose: The paper focuses on an aspect of disaster often overlooked by experts: that of disaster memory both as a prevention tool and one potentially contributing to the resilience of vulnerable communities in Japan. The objective is, more specifically, to explore one specific source of disaster memory in Japan, namely the disaster-related stone monuments scattered throughout the archipelago. Design/methodology/approach: To achieve the goals, the authors have studied several types of materials. First, the authors have used the "Natural Disaster Monument" online database compiled by the Geospatial Information Authority of Japan (GIS), data upon which the authors based the field research study, focused on water-related disaster in Otsu city (Shiga Prefecture). Simultaneously, the authors have systematically searched Japanese newspapers since the middle of the 19th century as well as the archives of Shiga prefecture in order to collect additional information on the statistical reality of these monuments, the context of their creation and in order to better estimate the severity of our case studies. Findings: First, the findings show that stone monuments are indeed structuring elements of disaster memory in Japan. Not only are they present throughout the archipelago, but in addition, they are still for the most part visited by local communities. Second, the findings show how this material culture of disaster, as a vector of disaster memory, could be used as a tool to better understand and bring awareness to the occurrence of specific hazards, especially to future generations. Originality/value: The authors promote an interdisciplinary approach by associating anthropology and history. The study offers a new and original character about an object of study relating to both the cultural and historical fields but still often neglected as a tool and object of research in DDR. The authors provide a method and suggest ways to integrate these stone monuments into DDR policies. Finally, the authors propose to better integrate these monuments into the overall reflection on disaster awareness and disaster mitigation.